Embodying Finance in Dreiser and DeLillo - Grgas-Mufa, Stipe (2012)
The presentation argued that through two characters in DeLillo's and Dreiser's novels we can see the differences of finance in the United States at two historical points but also the sameness of this category of capital
Neobjavljeno predavanje.
Projekt MZOS
ENG